Proyecto de factibilidad para la creación de una empresa productora y comercializadora de ventanas fabricadas con perfiles en base a poli cloruro de vinilo (PVC) ubicada en el parque industrial de Carcelén en la ciudad de Quito. - Álvarez Toapanta, Edison Leonardo (2014)
In its extension has established the commercial, technical, organizational and financial feasibility of the project for production and marketing of PVC windows in the city of Quito, for as soon as there is a significant unmet demand for these products and the product has competitive advantages with respect to the substitutes; in the middle is possible provided with the material, human and technical resources to produce the windows in PVC; it may be legally the company that would manage the project, and define a formal organizational structure and parameters to minimize the risk of failure; the evaluation indicators established its financial profitability and low risk, all these criteria has allowed recommend Its implementation, the same that would generate negative environmental impacts irrelevant, so it would require implementing the mitigation measures proposed, so that the social impact is maximized, and has the effect of improving the community’s quality life.